Dinamika Konsumsi Rokok Dan Impor Tembakau Indonesia - Antik Suprihanti; Harianto Harianto; Bonar M. Sinaga; Reni Kustiari (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
The tobacco control and the danger of smoking campaigns have given quite much impact into the lower nicotine and tar cigarettes consumption pattern. This fact affects the higher demand of imported tobacco in which are believed to be better than locals. Object of this research are to analyze trend of Indonesian tobacco import in the next 3 years and analyze factors that influence Indonesian tobacco import. Method of the research used descriptive method which using time series secondary data for 27 years from 1990 to 2016. Data is taken from few institusions and literatures. Analysis method used linier trend and multiple linier regression. Results of this research indicate that from 2018 to 2020 import of Indonesian tobacco trend will increase about 3 percent every year. Consumption of cigarettes kretek industries, income and import tariff affect to Indonesian tobacco import significantly. The increasing of imported tobacco is caused by the high demand of virginia tobacco of cigarettes industries that increased their cigarettes production cause high consumption of mild (low nicotine and tar) cigarettes. Therefore, Indonesia government has to support tobacco’s farmer in developing low nicotine and tar tobacco production that is needed by cigarettes industries through cooperation partnership with cigarettes producer, so the dependency of imported tobacco can be decreased.